Factor Structure, Internal Consistency and Criterion Validity of the Full-form and Short-form Versions of the Centrality of Events Scale in Young People - Galán, Santiago; Castarlenas, Elena; Racine, Mélanie; Sánchez-Rodríguez, Elisabeth; Tomé-Pires, Catarina; Jensen, Mark; Miró, Jordi (John Wiley & Sons, Ltd., 2017)
The perceived centrality of a traumatic event has been hypothesized to impact subsequent responses to that event and shown to be positively associated to a number of psychological problems. In order to understand the role of this construct in adjustment to stress and trauma, reliable and valid measures are needed. The objective of this study was to evaluate the factor structure, internal consistency and convergent validity of the full-form and short-forms of the Centrality of Event Scale when used with young people. A sample of 262 undergraduate students completed this study. Confirmatory factor analyses, Cronbach alpha coefficients and Pearson correlation coefficients were performed. The findings support a one-factor structure of the full 20-item and the short 7-item versions. We also found that both versions provide reliable and valid scores when used with young people. We recommend the use of the 7-item version to minimize assessment burden.
https://openpolicyfinder.jisc.ac.uk/id/publication/467?from=single_hit
Keywords: Psicometría; Psicología cognitiva; Centrality of Events Scalefactor structure; Young people; Factor structure; Internal consistency; Convergent validity